Acute Kidney Injury by SARS-CoV-2 virus in patients with COVID-19: an integrative review - Matheus Santos Moitinho; Angélica Gonçalves da Silva Belasco; Dulce Aparecida Barbosa; Cassiane Dezoti da Fonseca (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to assess scientific evidence on SARS-CoV-2 Acute Kidney Injury in patients with COVID-19. Methods: an integrative review, with adoption of PICO strategy and classification of the level of evidence, carried out on April 10, 2020 in the PubMed database, of articles available between December 2019 and April 2020. Results: the sample consisted of six original, five observational and one experimental articles. Observational studies addressed the clinical findings of patients with COVID-19 and association between kidney damage, infection, and morbidity-mortality. Conclusion: the studies addressed the mechanism of intracellular infection of SARS-CoV-2, its cytopathic effects on kidney cells and incidence of acute kidney injury in patients infected with SARS-CoV-2. Acute kidney injury is associated with increased mortality and morbidity in these patients. This review realizes the need for new research that can mention kidney care to patients with COVID-19.